PERLINDUNGAN HUKUM TERHADAP PENCIPTA LAGU â€œLAGI SYANTIKâ€ ATAS PERUBAHAN LIRIK TANPA IZIN PEMEGANG HAK CIPTA - Lully Tiyas Junita (Fakultas Hukum Universitas Islam Malang, 2021)
Copyright is an exclusive right that arises automatically based on declarative principles after the creation is in real or visualized form. Legal protection for songwriters is regulated in Law Number 28 of 2014 concerning Copyright. This research covers two main problems. First one, how is the implementation of copyright infringement on the song